2002
DOI: 10.1002/ccd.10296
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term renal function preservation after renal artery stenting in patients with progressive ischemic nephropathy

Abstract: We assessed the long-term effect of successful renal artery stent revascularization on renal function, blood pressure control, and survival in patients with progressive renal dysfunction due to ischemic nephropathy. Ischemic nephropathy presents a potentially serious risk of complete loss of renal function. Surgical renal revascularization is associated with significant risk of mortality/morbidity in this patient population. The potential role and long-term effect of renal artery stent revascularization in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 57 publications
6
48
0
4
Order By: Relevance
“…We excluded patients who would not benefit from renal revascularization (ie, patients with significant renal atrophy and azotemia with unilateral renovascular disease and bilateral functioning kidneys). Rocha-Singh, et al 16) , who had similar criteria as ours, observed similar results. Rodriguez, et al 26) observed the stent had no effect on renal function, in their hypertensive patient population that had normal renal function.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We excluded patients who would not benefit from renal revascularization (ie, patients with significant renal atrophy and azotemia with unilateral renovascular disease and bilateral functioning kidneys). Rocha-Singh, et al 16) , who had similar criteria as ours, observed similar results. Rodriguez, et al 26) observed the stent had no effect on renal function, in their hypertensive patient population that had normal renal function.…”
Section: Discussionsupporting
confidence: 86%
“…The effectiveness of renal intervention has been previously reported to be 42-91%. 10,12,14,16,22,26) In contrast, van Jaarsueld, et al randomized 106 cases into a drug or angioplasty group and observed no difference between the groups. 27) However, in their study, in 44% of the cases, renal angioplasty had been performed for uncontrolled hypertension despite a combination of three medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials have documented that renal artery stent placement improves or stabilizes renal function in patients with atherosclerotic RAS (749)(750)(751)(752). Significant improvement in renal function up to 1 year after unilateral renal artery stent placement was demonstrated by Leertouwer and coworkers (701).…”
Section: Class Iib Percutaneous Revascularization May Be Considered Fmentioning
confidence: 98%
“…9 Nonetheless, predictable benefit from renal revascularization may be most pronounced in individuals with renovascular disease that affects the entire renal mass-that is, both kidneys or a solitary kidney. 10 The extent to which renal artery disease affects death rate and renal dysfunction is not well defined. Studies of Medicare beneficiaries starting renal replacement therapy (renal dialysis or transplantation) indicate that 5% to 10% of these individuals have identified renovascular disease.…”
Section: Ischemic Nephropathy: Selecting Patients For Treatmentmentioning
confidence: 99%